GENE NETWORKS CONTROLLING ANTHER TAPETUM DEVELOPMENT IN BARLEY (Hordeum vulgare) DURING EARLY ANTHER DEVELOPMENT - HUA, Miaoyuan (2021)
The tapetum, the innermost somatic cell layer in anther locule, directly communicates with the developing gametophytic cells, providing essential nutrients, critical components for their development and maturity. The cell fate of the Arabidopsis tapetum is determined by a EMS1-SERK-TPD1 receptor-like kinase (RLK) signaling cassette, with similar control described in rice. After the cell fate has been determined, the tapetum starts its further development and subsequent programmed degeneration process to provide pollen coat essential materials for the developing pollen grains. Studies have shown a relatively conserved regulatory genetic pathway, DYT1-TDF1-AMS-MS188-MS1, controlling these complex events in Arabidopsis and rice.